2010
DOI: 10.1002/bem.20587
|View full text |Cite
|
Sign up to set email alerts
|

The association between exposure determined by radiofrequency personal exposimeters and human exposure: A simulation study

Abstract: The selection of an adequate exposure assessment approach is imperative for the quality of epidemiological studies. The use of personal exposimeters turned out to be a reasonable approach to determine exposure profiles, however, certain limitations regarding the absolute values delivered by the devices have to be considered. Apart from the limited dynamic range, it has to be taken into account that these devices give only an approximation of the exposure due to the influence of the body of the person carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 28 publications
3
77
2
4
Order By: Relevance
“…We also demonstrated that the concurrent use of two on-body calibrated exposimeters provides exposure levels (for most of the measured frequency bands) nearly up to 2-3 times higher than those provided with a single non-on-body calibrated exposimeter. This is in line with earlier studies (Bolte et al, 2011;Neubauer et al 2010;Thielens et al 2015a) that demonstrated that a non-on-body calibrated exposimeter will underestimate personal exposure to incident RF EMFs due to the shielding of the body.…”
Section: 1supporting
confidence: 92%
See 3 more Smart Citations
“…We also demonstrated that the concurrent use of two on-body calibrated exposimeters provides exposure levels (for most of the measured frequency bands) nearly up to 2-3 times higher than those provided with a single non-on-body calibrated exposimeter. This is in line with earlier studies (Bolte et al, 2011;Neubauer et al 2010;Thielens et al 2015a) that demonstrated that a non-on-body calibrated exposimeter will underestimate personal exposure to incident RF EMFs due to the shielding of the body.…”
Section: 1supporting
confidence: 92%
“…Neubauer et al (2008) suggested that frequency-specific calibration factor(s) should be applied while estimating RF-EMF exposures because RF-EMF exposures close to the human body are otherwise underestimated, which depends on the dimension of the human body, positions of the body-worn exposimeter(s) and frequency types. We have not reported the individual exposures measured by the ExpoM-RFs for summary statistics.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…However, exposure evaluations with exposimeters still have limitations (Bhatt et al, 2015), which give rise to measurement uncertainties. The uncertainties can reach up to 25-30 dB (Bolte et al, 2011;Iskra et al, 2011;Neubauer et al, 2010) and include shielding effects of the human body, the multidirectional nature of the incident RF-EMFs, residual calibration, the frequency response of the exposimeter, and the inability to detect signals below the lower detection limits, etc. (Bolte et al, 2011;Gajšek et al, 2015;Iskra et al, 2011 ;Mann, 2010;Neubauer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%